Optimization of process parameter for commercially pure aluminium alloy during friction stir deformation. Issue 2 (3rd April 2022) - Kumar, Binit; Sahu, Rohit; Mishra, Mukesh
ABSTRACT: Commercially pure aluminium is a prominent material for aviation, construction and automotive industries; however, its poor mechanical properties have restricted its usages. Friction stir process (FSP) is a novel technique of metal strengthening. Process parameters likes rotational speed, travelling speed and probe depth etc. affects the quality of the deformed zone and consequently on the properties of deformed material. In the present study commercially pure aluminium was subjected to FSD using CNC milling machine. A mild steel tool was carefully chosen and fabricated to have uniform defect free stir zone. The present study aimed to optimise the processing parameters for generating internal defect-free stir zone. The macrostructure observations of transverse cross-section were used to get an indication of the stir zone quality. Micro hardness of stirred samples were also evaluated and correlated with the all processing parameters. The result showed that improved mechanical property (Hardness is improved by 68%) with defect-free stir zone was observed at 1500 rpm rotational speed, 2 mm/min travelling speed and at 1.2 mm probe depth. Likewise through this process crystallite size was refined to 36 micron metre in a single pass from the underlying crystallite size of 96 micron metre.